Why the principle of informed self-determination does not help local farmers facing land loss: a case study from oil palm development in East Kalimantan, Indonesia. Issue 4 (18th May 2020) - Urano, Mariko
ABSTRACT: The principle of informed self-determination has been celebrated as a means to prevent involuntary land transfer and the resulting dispossession of affected communities in agricultural investments of developing countries. Based on qualitative field research conducted in East Kalimantan, Indonesia, this paper argues that such optimistic recognition needs reexamination. Drawing on a case study of indigenous Dayak communities that have faced advancement of large-scale oil palm estates since 2007, the paper examines what informs communities' decisions to release land to estates. The underdevelopment created by government neglect and the lack of future prospects for autonomous development are shown to have contributed to communities' decisions to release land. After a decade, encroaching palm oil has produced land shortages and depleted forest resources. This study highlights the need for meaningful state interventions to alleviate poverty and create conditions that allows local communities to make meaningful choices during the consultations over land release.